Carrier screening by next‐generation sequencing: health benefits and cost effectiveness. Issue 3 (29th January 2016) - Azimi, Mohammad; Schmaus, Kyle; Greger, Valerie; Neitzel, Dana; Rochelle, Robert; Dinh, Tuan
Abstract: Background: Compared with conventional genotyping, which typically tests for a limited number of mutations, next‐generation DNA sequencing (NGS) provides increased accuracy for carrier screening. The objective of this study was to evaluate the cost effectiveness of carrier screening using NGS versus genotyping for 14 of the recessive disorders for which medical society guidelines recommend screening. Methods: Data from published literature, population surveys, and expert opinion were used to develop a decision tree model capturing decisions and outcomes related to carrier screening and reproductive health. Results: Modeling a population of 1, 000, 000 couples that was representative of the United States population and that contained 83, 421 carriers of pathogenic mutations, carrier screening using NGS averted 21 additional affected births as compared with genotyping, and reduced costs by approximately 13 million. As compared with no screening, NGS carrier screening averted 223 additional affected births. The results are sensitive to assumptions regarding mutation detection rates and carrier frequencies in multiethnic populations. Conclusion: This study demonstrated that NGS‐based carrier screening offers the greater benefit in clinical outcomes and lower total healthcare cost as compared with genotyping. Abstract : We evaluated the cost effectiveness of carrier screening via next‐generation DNA sequencing (NGS) versus the traditional genotyping approach by using a robust mathematical model to estimate carefully selected health and other outcomes associated with 14 genetic diseases that major medical societies recommend for screening. The model accounts for all decisions considered by available medical opinion and outcomes relevant to carrier screening and reproductive health, drawing insight from the published literature, available clinical opinion, and subject matter experts.